Handbook of nanoscience, engineering, and technology - Goddard, William A., III, 1937- (CRC Press, 2012)
In his 1959 address, "There is Plenty of Room at the Bottom," Richard P. Feynman speculated about manipulating materials atom by atom and challenged the technical community "to find ways of manipulating and controlling things on a small scale." This visionary challenge has now become a reality, with recent advances enabling atomistic-level tailoring and control of materials. Exemplifying Feynman's vision, Handbook of Nanoscience, Engineering, and Technology, Third Edition continues to explore innovative nanoscience, engineering, and technology areas. Along with updating all.
Keywords: Nanotechnology -- Handbooks, manuals, etc.; Nanoscience.; elektronické knihy; electronic books